Application of 3D Prototyping to Promote Size-Inclusive Design Practices for Plus-Size Apparel. (2nd January 2022) - Hudson, Keena; Hwang, Chanmi
Abstract: Although innovative computer-aided design tools offer opportunities for advancing size-inclusive apparel design, minimal design research has been conducted to document the applications of these technologies. The purpose of this study is to identify plus-size women's needs through mixed method research and to integrate 3D prototyping technology to enhance plus-size apparel design. The research includes a) an online survey of plus-size consumers and market analysis to identify clothing needs and perceived problems, and b) development of a virtual and physical prototype through technology integration methods. This study responds to current needs to enhance apparel design for plus-size consumers; the integration of 3D prototyping and the functional, expressive, and aesthetic (FEA) process is a novel approach that places plus-size women at the center of the model. Results from this study may also provide practical guidelines for designers and students with limited knowledge of plus-size women's body types and bolster their interest in designing for larger body figures to promote a sense of inclusivity.